Guinea : Staff Report for the 1999 Article IV Consultation and Request for the Third Annual Arrangement Under the Enhanced Structural Adjustment Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The Guinean government faced economic management problems. The government revised its budget and adopted fiscal and monetary targets aimed at stopping monetary expansion by scaling back and controlling expenditure to meet revenue. Repayment of government debt to the central bank will increase private sector credit and the rebuilding of foreign exchange reserves. Exchange rate policy must be more clearly defined. Governance issues remain an important concern in Guinea. The enhanced Initiative for Highly Indebted Poor Countries (HIPC) will provide important debt relief to Guinea.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet